Mobile network sharing trends in developing and developed mobile markets (regulations and market forces): A comparison between selected Latin American markets and Sweden - Juan Pablo Lasso; Ashraf Awadelkarim Widaa Ahmed; Jan Markendahl (International Telecommunications Society (ITS), 2013)
The present document has the objective of analyzing the impact of several factors that are part of mobile telecom markets into the feasibility of sharing resources as a strategy for operators to deploy their networks in a cost-efficient manner and cope with the ever increasing amount of data traffic. These factors include the situation of the operators with their distribution of market shares, the nature of national regulatory authorities, and their lines of action. The study comprises the description and analysis of three markets: Ecuador, Chile, and Sweden, as they pose very different scenarios and are useful to prove the contrast present in two different regions of the world. The results of this research work show that in order to ease the adoption of network sharing in a market, a state of fair competition must be encouraged, reflected by a good distribution of market shares between operators. This is for the most part a task of the regulators, as they must make sure to award resources to operators in an equitable manner, as well as to identify the right moments to introduce new actors into the market, as it is observed in the cases of Chile and Sweden. Additionally, the regulators must have a liberal approach in their decisions, by permitting both active and passive network sharing, as this study shows that this is not the case in Chile and Ecuador so far.
Keywords: 330